Understanding SAF-A's role in chromatin organisation throughout the cell cycle and in a rare neurodevelopmental disorder - Lazarova, Elena (The University of Edinburgh, 2024)
Large-scale chromatin organisation during interphase and mitosis has been extensively studied; however, the mitotic exit remains poorly understood. This thesis aims to elucidate the involvement of the essential protein Scaffold Attachment Factor A (SAF-A; also called HNRNPU) in chromatin organisation during the mitotic exit and its impact on cellular phenotypes, particularly in the context of HNRNPU-related neurodevelopmental disorder. SAF-A regulates interphase chromatin structures in a transcription-dependent manner. The protein can decompact gene-active regions by interacting with chromatin-associated RNAs and binding ATP to form protein oligomers. SAF-A's eviction from mitotic chromosomes suggests it might have a precise recruitment to gene-active regions for establishing and maintaining the RNA mesh after mitosis. Additionally, perturbations in SAF-A function may result in faulty chromatin architecture at gene-active regions, contributing to cellular phenotypes observed in patients with HNRNPU-related neurodevelopmental disorder. To investigate whether transcriptional events during telophase or in early G1 recruit SAF-A, I used a live cell imaging system and co-localisation analysis. Imaging cells going through mitosis showed that SAF-A is recruited to chromatin during cytokinesis and inhibiting transcription at that time delayed its recruitment to early G1. This allowed the examination of SAF-A's association with RNAs during mitosis and mitotic exit using synchronized cells. In comparison with monomeric SAF-A, more oligomeric SAF-A was associated with new and old RNA during mitosis and early G1, showing that the protein regulates large-scale chromatin organisation as soon as it is recruited during mitosis. Next, I investigated the interaction between SAF-A and RNA and whether SAF-A depletion affects the RNA mesh in interphase. Depleting SAF-A with RNAi treatment resulted in a reduced RNA mesh density and connectivity. Finally, the effect of SAF-A mutations, from patients with the HNRNPU-related neurodevelopmental disorder, on chromatin organisation was explored. Human cell lines expressing mutated SAF-A proteins were generated, and their impact on chromatin decompaction was quantified using FISH with each mutant having a different phenotype. This thesis sheds light on the behavior of SAF-A at the mitotic exit and provides insights into its role in large-scale chromatin organisation. Furthermore, it investigates the cellular phenotypes associated with SAF-A patient mutations, contributing to our understanding of the underlying mechanisms and potential therapeutic targets for HNRNPU-related neurodevelopmental disorder.
Keywords: SAF-A; cytokinesis; SAF-A mutation; brain development; mitotic exit; Scaffold Attachment Factor A; faulty chromatin architecture; chromatin decompaction